Advanced Electronics: The Emergence, Evolution, and Future of Gallium Nitride Technology - Xiong, Weixiang (Transactions on Computer Science and Intelligent Systems Research, 2024)
Gallium nitride (GaN) is a desirable substance for electronics that require high frequencies and high power. The research and development of vertical GaN devices on GaN substrates has made significant progress in recent years, thanks to the availability of high-quality free-standing bulk GaN substrates. Despite some inherent difficulties associated with substrate fabrication and the intricate process of metal doping for sensor applications, the prospects for the future of GaN appear quite encouraging. As a result, various transistors and diodes with excellent characteristics have been reported. This essay explores the trajectory of Gallium Nitride (GaN) and its transformative influence on the field of electronic technology. It starts from the distinctive characteristics of GaN, including its broad bandgap, Wurtzite structure, and remarkable thermal conductivity, within the framework of its historical progression, spanning from its initial synthesis to its significant contribution to energy-efficient lighting and 5G technologies. The progress made in the manufacturing processes of GaN, which have shifted towards more sustainable and efficient methods, is also discussed. It also explores the innovative applications of GaN in high-frequency power electronics and optoelectronics, emphasizing its importance in enhancing device efficiency and facilitating environmental monitoring.